Analyzing Gender Stereotypes in Eva Ibbotson's Which Witch? (1992) - Zahra Nurul Aliyyah (Passage, 2018)
Gender stereotypes are notorious for their harmful effects; yet, the stereotypesare still found and encouraged through many aspects of life, including literaryworks such as children’s literature. This present study examines a children-targeted novel to find whether the book conforms or goes against genderstereotypes. The novel examined is written by Eva Ibbotson and titled WhichWitch? (1992). The present study specifically analyzes the gender stereotypicaltraits and attributes found in the characterization of the characters. To analyze thedata, Evan-Davies’ (2000) and Copenhaver’s (2002) lists of traits and attributeshave been drawn on. The study reveals that the book seems to perpetuate andpromote gender stereotypes by embedding gender stereotypical traits andattributes in the characterization of the protagonists of the novel. Keywords: gender stereotypes, children’s literature, gender-stereotypical traits and attributes